1988
DOI: 10.1016/0014-5793(88)80835-4
|View full text |Cite
|
Sign up to set email alerts
|

Is the 9 kDa thylakoid membrane phosphoprotein functionally and structurally analogous to the ‘H’ subunit of bacterial reaction centres?

Abstract: Although the amino acid sequence of the 9 kDa (phospho)protein of chloroplasts has been determined, the function of this thylakoid membrane protein in photosynthetic electron transport and the reason for its physiological control remains unclear. In this paper, I briefly review the evidence which indicates that the phosphorylation of the 9 kDa protein results in a partial inhibition of photosynthetic oxygen evolution by increasing the stability of the semiquinone bound to QA the primary, plastoquinone‐binding … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

1989
1989
1997
1997

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 41 publications
1
10
0
Order By: Relevance
“…Such a role would assume the location of the 9-kDa protein in the close proximity of the D1 protein where it could directly affect the QB site. We have not, however, found sufficient sequence homology between the Synechocystis 6803 PsbH protein and the reaction center H-subunit of purple photosynthetic bacteria to suggest these proteins evolved directly from a common ancestral protein as proposed by Packham (1988).…”
Section: Discussionmentioning
confidence: 80%
“…Such a role would assume the location of the 9-kDa protein in the close proximity of the D1 protein where it could directly affect the QB site. We have not, however, found sufficient sequence homology between the Synechocystis 6803 PsbH protein and the reaction center H-subunit of purple photosynthetic bacteria to suggest these proteins evolved directly from a common ancestral protein as proposed by Packham (1988).…”
Section: Discussionmentioning
confidence: 80%
“…There have been many functions proposed for the phosphorylated form such as protection of the protein from chloroplast aminopeptidases as a means of stabilizing the PSII complex [33]. It has also been suggested that phosphorylation of PSII-H, after having supported plastoquinone interaction and reduction at the QB site, would change the conformation of the QB pocket to reduce plastoquinone binding [35]. Finally, phosphorylation of the PSII-H protein (along with the other Photosystem II proteins) has been proposed to be involved with increasing the charge repulsion against phosphorylated LHC apoproteins, triggering the dissociation of the peripheral antenna complexes and thereby regulating light energy utilization [3,4].…”
Section: Discussionmentioning
confidence: 99%
“…Packham (1988) proposed that PSII-H is the PSII counterpart to the H subunit of reaction centers of photosynthetic www.plantphysiol.org on May 11, 2018 -Published by Downloaded from Copyright © 1997 American Society of Plant Biologists. All rights reserved.…”
Section: Discussionmentioning
confidence: 99%